2008
DOI: 10.1073/pnas.0801232105
|View full text |Cite
|
Sign up to set email alerts
|

Genetically encoded photoswitching of actin assembly through the Cdc42-WASP-Arp2/3 complex pathway

Abstract: General methods to engineer genetically encoded, reversible, light-mediated control over protein function would be useful in many areas of biomedical research and technology. We describe a system that yields such photo-control over actin assembly. We fused the Rho family GTPase Cdc42 in its GDP-bound form to the photosensory domain of phytochrome B (PhyB) and fused the Cdc42 effector, the Wiskott-Aldrich Syndrome Protein (WASP), to the light-dependent PhyB-binding domain of phytochrome interacting factor 3 (Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 35 publications
2
75
0
Order By: Relevance
“…1E, F). These results show clearly that constitutively active Cdc42 binds the CRIB domain of WASP, whereas a dominant-negative form of Cdc42 has very low binding-affinity (22,23). Thus, we confirmed that ECLIPSE represents an effective method for monitoring constitutive P-P interactions in live mammalian cells.…”
Section: Resultssupporting
confidence: 67%
“…1E, F). These results show clearly that constitutively active Cdc42 binds the CRIB domain of WASP, whereas a dominant-negative form of Cdc42 has very low binding-affinity (22,23). Thus, we confirmed that ECLIPSE represents an effective method for monitoring constitutive P-P interactions in live mammalian cells.…”
Section: Resultssupporting
confidence: 67%
“…Fusion of an Arabidopsis cryptochrome with a DNA damage checkpoint protein even enabled the activation of the DNA damage signaling pathway in the absence of DNA damage (Ozkan-Dagliyan et al 2013). Also the light-inducible interactions between phytochrome and the phytochrome interaction factor 3 (PIF3) (Leung et al 2008;Tyszkiewicz and Muir 2008) or the LOV-containing F-box proteins FKF1 and its partner GIGANTEA (Yazawa et al 2009) have been used to regulate various cellular activities. A light-switchable gene promoter system should also be mentioned, which was constructed using an Arabidopsis phytochrome; this system allows for reversible control of gene expression with red and far-red light (Shimizu-Sato et al 2002).…”
Section: Application Of Light-sensitive Modules In Synthetic Biology mentioning
confidence: 99%
“…Precise control and perturbation over cellular fate and activities such as neuronal firing, 19,20 activation of specific signaling cascades, [21][22][23] gene transcription, 24 protein production, 25 and modulation of proteinprotein interactions 26 in living cells and organisms have been achieved using light signals. These light-based methods can modulate individual cell behaviors at the subcellular level with high time resolution, allowing for quantitative dynamic information on cellular processes to be Knowing that the co-expression of YFP-Parkin and KillerRed-dMito is well tolerated by cells, we then tested the use of KillerRed protein for spatiallyencoded ROS generation in living cells using a well-established ROS sensor: 2,7-Dichlorodihydrofluorescein diacetate (DCF).…”
Section: Resultsmentioning
confidence: 99%